GRATITUDE AS A POSITIVE CHARACTER STRENGHTS: HOW TO DEVELOP AS AN ADOLESCENT WITH IN ROLE OF A SCHOOL COUNSELOR - Garnika; Adiwinata, Anne Hafina; Yustiana , Yusi Riksa (EDUCATIONE, 2023)
Gratitude is one of the virtues transcendence character strengths that can help adolescents achieve a higher quality of life. Adolescents who have a high level of gratitude will have greater life satisfaction, joy, and well-being, being able to live a more positive life. The state of today's adolescents , who are prone to developing mood disorders such as worry, stress, and depression in dealing with life's issues, exemplifies the phenomena of low gratitude. The purpose of this study is to figure out how school counselors might help adolescents develop gratitude by offering psycho-educational services. A comprehensive literature review using content analysis methodologies was utilized to determine the role of school counselors in undertaking intervention activities to develop adolescent gratitude. 10 key research papers were examined in the study. The study's findings provide a conceptual framework for psycho-educational services based on particular training such as counting blessings, three good exercises , and a gratitude visit that school counselors can use to assist adolescent cultivation of gratitude. This study can serve as a model for future studies on to develop adolescent gratitude.